2023
DOI: 10.18178/ijiet.2023.13.2.1802
|View full text |Cite
|
Sign up to set email alerts
|

Applying Gamification Technique and Virtual Reality for Prehistoric Learning toward the Metaverse

Abstract: Technological development provides many benefits in learning process, such as the development of the learning method, media, strategy, and design. Based on the observation had been done at History department, UNDIKSHA showed that the students had problems in learning process especially in Indonesian Prehistory Course. The lecturer still focused on teacher-centered method and book only without using technological development. That is why, students’ interest, motivation, and understanding towards the learning pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It provides visitors with information, which is upto-date, complete, simply comprehensible, and matches the information requirement enhances a visitor's degree of satisfaction. So, AR technology helps museums obtain attractiveness by facilitating visitors to achieve experiences that are concurrently aesthetically educational and entertainment [86].…”
Section: A Measurement Modelmentioning
confidence: 99%
“…It provides visitors with information, which is upto-date, complete, simply comprehensible, and matches the information requirement enhances a visitor's degree of satisfaction. So, AR technology helps museums obtain attractiveness by facilitating visitors to achieve experiences that are concurrently aesthetically educational and entertainment [86].…”
Section: A Measurement Modelmentioning
confidence: 99%
“…Research discussions on gamification in metaverse learning are relatively limited, but recent studies have begun to explore this area [10,[36][37][38]. For instance, Muthmainnah et al's research suggests that gamification elements in metaverse learning scenarios positively impact student engagement, transforming learning into an enjoyable experience [10].…”
Section: Gamification and Learning Motivation In The Metaversementioning
confidence: 99%
“…For instance, Muthmainnah et al's research suggests that gamification elements in metaverse learning scenarios positively impact student engagement, transforming learning into an enjoyable experience [10]. Agustini et al's study found that gamification enhances student motivation and initiative, providing students with a more immersive learning experience in metaverse settings [37].…”
Section: Gamification and Learning Motivation In The Metaversementioning
confidence: 99%
“…It is apparent from the network that the red cluster is the most significant, as it contains the highest number of keywords. This cluster focuses on the intersection of immersive technologies, education, and the implications of the metaverse on the human experience [3,6,105]. This multifaceted concentration encompasses various dimensions, including the development and deployment of VR, AR, and MR technologies as well as the rise of XR as a unified framework [106,107].…”
Section: Abstract and Keyword Co-occurrence Analysismentioning
confidence: 99%